Developing station DYUP as a communication support to the fisheries and marine science program of UP in the Visayas - Daquilanea, Amy D.
This study aims to established the need for and feasibility of developing Station DYUP as communication support to the fisheries program of UP in the Visayas., DYUP at present functions as a laboratory for Broadcasting students' exposure to radio production. As proposed, the station will be used as a communication support to the fisheries program of UP Visayas. This study comes in two parts. The first part establishes the need to develop station DYUP. Part I was done through a survey conducted among 401 fishermen from six coastal barangays of the three sample municipalities, namely, Miagao, Dumangas and Estancia. Similarly, eight station managers of the local radio stations and 55 heads of government offices/agencies in the province of Iloilo were surveyed to find out their willingness to support station DYUP. Findings show that there is definitely a need to develop station DYUP as a communication support to the fisheries program of UP in the Visayas as evidence by a high frequency of positive response to the proposal and the willingness to listen to and support the station. The second part of the study conceptualizes the feasibility of developing station DYUP that best fulfills the demand posed in Part I. Part II outlines a feasibility study which include technical, education, budget and finance, integration, programming, promotions and management factors. On the whole, this feasibility study could serve as a guide for UP in the Visayas in an attempt to expand station DYUP's role as a communication support to its fisheries and marine science program.